Cardiotoxicity and multiorgan system failure caused by valproate poisoning: case report and review of the literature - Letonja, Mitja; Petrovič, Danijel (Acta Medico-Biotechnica, 2021)
We report the case of severe valproate intoxication presenting as multiorgan failure. This is the first report to describe severe cardiac involvement, in which a 19-year-old woman developed atrial fibrillation, diffuse T wave inversion and QTc interval prolongation with elevated specific biochemical markers of myocardial damage. After 7 days of treatment, including supportive care, gastric lavage, activated charcoal, mannitol and hemodialysis, the patient recovered completely. After the poisoning there were no pathological echocardiographic changes and one month after discharge exercise stress testing did not provoke ischemia or arrhythmias.